2023
DOI: 10.3389/fgwh.2023.988328
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitude of women towards maternity waiting homes and associated factors among women who gave birth in the last twelve months in Dega Damot district, northwest Ethiopia

Abstract: BackgroundMaternal waiting homes have been identified as one strategy to reduce maternal and perinatal mortality by bringing women living in hard-to-reach areas closer to a health facility that provides emergency obstetric care. Even if utilization of maternal waiting homes is repeatedly assessed, there is a scarcity of evidence in Ethiopia regarding women's knowledge and attitude towards maternal waiting homes.ObjectiveThis study aimed to assess women's knowledge and attitude towards maternity waiting homes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Use of MWHs also depends largely on male partners’ decisions 18 , 19 . Furthermore, a study from Northwest Ethiopia showed that antenatal care (ANC) visits, short distance to health facilities, women’s involvement in decision making, and MWH use were found to be associated with maternal knowledge, whereas higher education status, ANC visits, and short distance to the facility were associated with maternal attitudes towards MWHs 20 . However, further studies are required to have a comprehensive understanding about factors associated with women’s knowledge and attitudes regarding MWHs in rural Ethiopia.…”
Section: Introductionmentioning
confidence: 99%
“…Use of MWHs also depends largely on male partners’ decisions 18 , 19 . Furthermore, a study from Northwest Ethiopia showed that antenatal care (ANC) visits, short distance to health facilities, women’s involvement in decision making, and MWH use were found to be associated with maternal knowledge, whereas higher education status, ANC visits, and short distance to the facility were associated with maternal attitudes towards MWHs 20 . However, further studies are required to have a comprehensive understanding about factors associated with women’s knowledge and attitudes regarding MWHs in rural Ethiopia.…”
Section: Introductionmentioning
confidence: 99%